Кримінально-правова характеристика умисного незаконного знищення, руйнування або пошкодження об’єктів культурної спадщини за законодавством України та країн Східної Європи - Герелюк, Тарас Бонданович; Герелюк, Тарас Бонданович; Gerelіuk, Taras B. (My University, 2021)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.08 – кримінальне право та кримінологія; кримінально-виконавче право. – Національний університет «Одеська юридична академія», Одеса, 2021. Дисертація є першим в Україні комплексним порівняльно-правовим дослідженням кримінально-правової характеристики умисного незаконного знищення, руйнування або пошкодження об’єктів культурної спадщини за законодавством України та країн Східної Європи. У дисертації висунуто і обґрунтовано низку нових теоретичних і важливих у практичному значенні положень, що відбивають її наукову новизну, зокрема, вперше: на основі історичного аналізу нормативно-правових актів та історіографічних здобутків виділені періоди становлення кримінально-правової охорони об’єктів культурної спадщини в Україні: 1) імперський – початок XX – 1917 р.; 2) період національно-визвольного руху – 1917–1921 рр.; 3) радянський – 1921–1991 р.; 4) сучасний – з 1991 року по теперішній час. До початку ХХ ст. відбувався поступовий процес накопичення матеріальних цінностей, створених людством, а також переосмислення культури та її матеріальних форм як необхідного аспекту розвитку спільнот та соціумів, що потребує охорони, в тому числі і на законодавчому рівні. Встановлено, що кримінальне законодавство країн Східної Європи пропонує різні підходи до визначення змісту предметів правової охорони. У цих країнах такі предмети злочинних посягань, як об’єкти культурної спадщини мають різне найменування: пам’ятники культури (КК Словаччини, Республіки Болгарія), витвори культури (КК Албанії), культурні цінності (КК Хорватії), національні цінності (КК Литовської Республіки), культурна спадщина (КК Північної Македонії) та ін. У деяких країнах Східної Європи предметом досліджуваного злочину стають не лише культурні чи історичні цінності (пам’ятки), а й природні об’єкти, наприклад, у КК Боснії і Герцеговини. Охорона культурної спадщини за законодавством Східної Європи носить фрагментарний характер. Знищення культурної спадщини у країнах, що змінили своє законодавство після підписання міжнародних конвенцій, зазвичай карається як військовий злочин, а також як злочин проти власності. Охорона культурної спадщини здійснюється за допомогою норм кримінального права щодо охорони культурної спадщини у період збройних конфліктів, воєнного стану та у мирний час. Установлено, що більшість кримінальних кодексів країн Східної Європи містить такий склад злочину, як знищення, руйнування або пошкодження об’єктів культурної спадщини у розділі злочини проти власності (Чорногорія, Сербія, Албанія та ін.). З’ясовано, що існують і виключення. Так, у КК Північної Македонії міститься окремий розділ, який має назву «Злочини проти культурної спадщини та природних раритетів». На підставі аналізу основних різновидів кваліфікуючих ознак умисного незаконного знищення, руйнування або пошкодження об’єктів культурної спадщини за законодавством України та країн Східної Європи встановлено, що норма ст. 298 КК України, а також більшість кваліфікованих видів такого злочину не є типовими для законодавства країн Східної Європи.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.08 – уголовное право и криминология; уголовно-исполнительное право. – Национальный университет «Одесская юридическая академия», Одесса, 2021. Диссертация является первым в Украине комплексным сравнительно-правовым исследованием уголовно-правовой характеристики умышленного незаконного уничтожения, разрушения или повреждения объектов культурного наследия по законодательству Украины и стран Восточной Европы. В диссертации выдвинут и обоснован ряд новых теоретических и важных в практическом смысле положений, отражающих ее научную новизну, в частности, впервые: на основе исторического анализа нормативно-правовых актов и историографических достижений выделены периоды становления уголовно-правовой охраны объектов культурного наследия в Украине 1) имперский – начало XX ст. – 1917 г.; 2) период национально-освободительного движения – 1917–1921 гг.; 3) советский – 1921–1991 гг.; 4) современный – с 1991 года по настоящее время. К началу ХХ в. происходил постепенный процесс накопления материальных ценностей, созданных человечеством, а также переосмысление культуры и ее материальных форм как необходимого аспекта развития сообществ и социумов. Установлено, что уголовное законодательство стран Восточной Европы предлагает различные подходы к определению содержания предметов правовой охраны. В этих странах такие предметы преступных посягательств, как объекты культурного наследия имеют различное наименование: памятники культуры (УК Словакии, Республики Болгария), произведения культуры (УК Албании), культурные ценности (УК Хорватии), национальные ценности (УК Литовской Республики), культурное наследие (УК Северной Македонии) и др. В некоторых странах Восточной Европы предметом исследуемого преступления становятся не только культурные или исторические ценности (памятники), но и природные объекты, например, в УК Боснии и Герцеговины. Охрана культурного наследия по законодательству Восточной Европы носит фрагментарный характер. Уничтожение культурного наследия в странах, которые изменили свое законодательство после подписания международных конвенций, обычно наказывается как военное преступление, а также как преступление против собственности. Охрана культурного наследия осуществляется с помощью норм уголовного права об охране культурного наследия в период вооруженных конфликтов, военного положения и в мирное время. Установлено, что большинство уголовных кодексов стран Восточной Европы содержат такой состав преступления, как уничтожение, разрушение или повреждение объектов культурного наследия в разделе преступления против собственности (Черногория, Сербия, Албания и др.). Выяснено, что существуют и исключения. Так, в УК Северной Македонии содержится отдельный раздел, который называется «Преступления против культурного наследия и природных раритетов». На основании анализа основных разновидностей квалифицирующих признаков умышленного незаконного уничтожения, разрушения или повреждения объектов культурного наследия по законодательству Украины и стран Восточной Европы установлено, что норма ст. 298 УК Украины, а также большинство квалифицированных видов такого преступления не являются типичными для законодательства стран Восточной Европы.

The dissertation for the degree of candidate of legal sciences, specialty 12.00.08 – Criminal Law and Criminology; Penal Law. – National University «Odesa Law Academy», Odesa, 2021. The thesis is the first comprehensive comparative legal study of the criminal law characteristics of the deliberate illegal destruction, destruction, or damage of cultural heritage objects under the legislation of Ukraine and Eastern European countries. The dissertation put forward and substantiated several new theoretical and important in a practical sense provision, reflecting its scientific novelty, in particular, for the first time: based on a historical analysis of normative legal acts and historiographic achievements, periods of the formation of the criminal legal protection of cultural heritage objects in Ukraine are highlighted 1) imperial – early XX – 1917; 2) the period of the national liberation movement – 1917–1921; 3) Soviet – 1921–1991; 4) modern – from 1991 to the present. By the beginning of the twentieth century, there had been a gradual process of accumulation of material values created by mankind, as well as a rethinking of culture and its material forms as a necessary aspect of the development of communities and societies. It is established that the objective side of the analyzed crime under the criminal law of Ukraine and Eastern Europe is characterized by an alternative indication of several possible forms: 1) destruction or 2) damage or 3) demolition. In addition, the use of three forms in Art. 298 of the Criminal Code of Ukraine is superfluous. We offer the word « demolition» to exclude from the text of Part 2 of Art. 298 of the Criminal Code of Ukraine. The criminal legislation of the countries of Eastern Europe offers different approaches to determining the content of objects of legal protection. In these countries, such objects of criminal encroachments as objects of cultural heritage have different names: cultural monuments (Criminal Code of Slovakia, Republic of Bulgaria), cultural works (Criminal Code of Albania), cultural values (Criminal Code of Croatia), national values (Criminal Code of the Republic of Lithuania), cultural heritage (Criminal Code of North Macedonia), etc. In some countries of Eastern Europe, the subject of the crime under investigation is not only cultural or historical values (monuments), but also natural objects, for example, in the Criminal Code of Bosnia and Herzegovina. Protection of cultural heritage under the legislation of Eastern Europe is fragmented. Destruction of cultural heritage in countries that changed their legislation after the signing of international conventions is usually punished as a war crime as well as a crime against property. The protection of cultural heritage is carried out with the help of the norms of criminal law on the protection of cultural heritage during armed conflicts, martial law and peacetime. It was highlighted that under the legislation of Ukraine and most Eastern European countries, subjectively, the crime of destruction, or damage of cultural heritage sites is characterized by an intentional form of guilt. The criminal law of other Eastern European countries is characterized by the existence of a separate rule on liability for negligent damage or destruction of cultural heritage sites (Republic of Belarus). The subject of the crime of destruction or damage of cultural heritage objects is, as a rule, a natural sane person who has reached a certain age at the time of commission the crime. On the basis of comparative legal research of qualifying features of crimes encroaching on objects of archeological and cultural heritage according to the legislation of Ukraine and the countries of Eastern Europe the qualifying features of destruction or damage of objects of cultural heritage are systematized. The following bases (criteria) of systematization are allocated: 1) on objective signs: on the grounds of the objective side of the act (action, consequence); 2) on subjective grounds: depending on the purpose; according to the characteristics of the subject. Based on the analysis of the main varieties of qualifying signs of deliberate illegal destruction or damage of cultural heritage objects according to the legislation of Ukraine and the countries of Eastern Europe, it was established that the norm of Art. 298 of the Criminal Code of Ukraine, as well as most of the qualified types of such crimes, are not typical for the legislation of the countries of Eastern Europe.
дис. ... канд. юрид. наук: 12.00.08
Герелюк Т.Б. Кримінально-правова характеристика умисного незаконного знищення, руйнування або пошкодження об’єктів культурної спадщини за законодавством України та країн Східної Європи: дис. ... канд. юрид. наук: 12.00.08 / Герелюк Тарас Богданович. Одеса, 2021. 205 с.
Keywords: кримінальне законодавство України; кримінальне законодавство країн Східної Європи; кваліфікація; кримінальне право; кваліфікуючі ознаки; склад злочину; злочин; об’єкт культурної спадщини; кримінально-правова норма; знищення; руйнування; пошкодження; уголовное законодательство Украины; уголовное законодательство стран Восточной Европы; уголовное право; уголовно-правовая норма; уничтожение; разрушение; повреждение; объект культурного наследия; преступление; состав преступления; квалифицирующие признаки; квалификация; qualifications; qualifying signs; corpus delicti; crime; cultural heritage object; damage; annihilation; destruction; criminal law; criminal legislation of Ukraine; criminal legislation of the countries of Eastern Europe